UPAYA PENINGKATKAN KUALITAS GARAP KOREOGRAFI ANAK MELALUI METODE INDIVIDUAL MAHASISWA JURDIK SENI TARI FBS UNY - Marwanto - (Imaji, 2007)
Children choreography is creating dances for children that are suitable with their ways of thinking and playing world. This research is aimed at improving quality of children choreography. The expectation is that the choreography might become subject of excellence and brings a good name to the Dance Art Education Department specifically and Yogyakarta State University generally. This study applied class action research, with students of Composition and Choreography II Classes in the even semester of 2005/ 2006 as its subject. The result shows that the students' academic achievement and the quality of their choreography increased significantly. Out of 22 students' creations, 4 are taken as models of dance learning in primary, junior high and senior high schools. Key words: Children choreography, subject of excellence